Analysis of viscosity effects in the moving bed and filter cake washing process - Rodríguez-Machín, Lizet; Hoffner, Berhard; Stahl, Werner (My University, 2005)
Washing particulate products in a moving bed is affected especially by the material properties, particularly the viscosities of the used liquids. In this work viscosity variations are achieved by the addition of Polyvinylpyrrolidone (PVP). Preliminary investigations show that the concentration of impurities can be clearly determined by a conductivity measurement, taking deviations due to the PVP-addition into account. Likewise it is demonstrated that in the considered temperature range the viscosity ratio N* of the wash to the mother liquid considered is constant. The experimental results showed for both used sand fractions that the transition area of the corresponding washing curves expand always to higher wash ratios outwards with decreasing viscosity ratio. If the viscosity ratios are 1/9 or 1/15 the transition area expands to such and extent that no diffusion domain appears within the parameter range investigated. In this case, the level of impurities is higher and the curves are positioned over the curve for cake washing with viscosity ratio *=1. This tendency leads to a less efficient washing process. If the mother liquor has a lower viscosity than the wash liquid, the extension of the transition area of the washing curve decreases and the washing results are better. Once the diffusion domain is reached, the level of impurity is identical for all the viscosity ratios, which is in the range of 0,3% of the initial impurity load. The comparison of the systematic viscosity variation of a cake washing process shows similar tendencies. The level of impurity in the diffusion domain is a factor 10 times higher for the filter cake washing when the viscosity ratio N* > 1.
Keywords: Cake Washing; Filtration; Moving Bed Washing; Purification; Separation; Viscosity